Corruption and distortion of public expenditures: Evidence from Africa - (:unkn) unknown (My University, 2021)
This study investigates the effect of corruption on the trade-off between capital and current expenditures in a panel of 48 African countries over the period 2000-2016.Based on statistical yearbooks, we compile disaggregated data on public finances for African countries and find that a high prevalence of corruption distorts the composition of public expenditures at the expense of the share of capital expenditure. Specifically, an increase in corruption by one standard deviation is associated with a decrease in the proportion of capital expenditure from 29\% to 16\%. The results are robust to various specifications and estimation methods, including the fixed effects and instrumental variables approach. The supportive argument demonstrates that it seems more beneficial for corrupted bureaucrats to manipulate public spending in favor of current rather than capital expenditures. The latter relies on formal and traceable procedures, whereas current expenditure is known to be more open to the use of discretionary allocation.
Keywords: African Research